Meanings of flower therapy for anxiety in people with overweight or obesity - Pancieri, Ana Paula [UNESP]; Fusco, Suzimar Benato [UNESP]; Abrantes Ramos, Bianca Ires [UNESP]; Braga, Eliana Mara [UNESP] (Assoc Brasileira Enfermagem, 2018)
Objective: To understand the experience from the perspective of the participant of a clinical research, which had as intervention the flower therapy for anxiety of individuals with overweight and obesity. Method: qualitative study, developed by semi-structured interview with 42 participants from a clinical research and data submitted to content analysis. Results: after analysis, five thematic categories emerged: seeking natural alternatives to aid in control of anxiety and obesity; perceiving the benefits of flower therapy in itself and in family and professional relationships; recognizing flower therapy as source of tranquility and self-knowledge; perceiving changes in sleep quality; acquiring self-control and guidance on food and relational needs. Final considerations: the participants showed the intention of seeking natural alternatives to aid the control of anxiety and obesity, employing complementary therapies to strengthen their health. Consequently, participants reported self-control in feeding and in family and professional relationships.
Keywords: Flower Essences; Clinical Trial; Qualitative Research; Anxiety; Obesity